The Blackwell Companion to the Sociology of Culture 2007
DOI: 10.1002/9780470996744.ch18
|View full text |Cite
|
Sign up to set email alerts
|

Counter-Memories of Terrorism: The Public Inscription of a Dramatic Past

Abstract: How can we remember terror, and how can we forget it? How can we commemorate it? What is the most suitable cultural shape of remembering terror? By addressing the issue of the social representation of very controversial pasts, this chapter addresses the relation between the collective knowledge and memories of terrorist attacks in Italy and the process of their being fixed and shaped into commemorative social practices and cultural objects. This process may reflect tensions and contradictions between state and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…When memories of trauma (large displacement of people, war, terror) are involved, this question of memory's shape can become urgent and the stakes around how memories take shape are high and the path to what is remembered can be highly dangerous. This is because memories are selective; they are formed in relation to what the sociologist Anna Lisa Tota calls 'technologies of memory' (Tota 2001(Tota , 2005 by which she means media-aesthetic and material forms that mediate and formulate memory, structuring perception of the past in ways that enhance some features and suppress others. What is remembered, in other words, is culturally arranged and that arrangement can both facilitate and constrain the pathways to which remembering can take us.…”
Section: Bringing With and Protectingmentioning
confidence: 99%
See 1 more Smart Citation
“…When memories of trauma (large displacement of people, war, terror) are involved, this question of memory's shape can become urgent and the stakes around how memories take shape are high and the path to what is remembered can be highly dangerous. This is because memories are selective; they are formed in relation to what the sociologist Anna Lisa Tota calls 'technologies of memory' (Tota 2001(Tota , 2005 by which she means media-aesthetic and material forms that mediate and formulate memory, structuring perception of the past in ways that enhance some features and suppress others. What is remembered, in other words, is culturally arranged and that arrangement can both facilitate and constrain the pathways to which remembering can take us.…”
Section: Bringing With and Protectingmentioning
confidence: 99%
“…The ways that commemoration rituals are negotiated inevitably selects, condenses and traduces the lived experience of what occurred and thus is inevitably politicised. Moreover, depending on how commemorations are configured, possibilities for the future-realising change and healing-will be constrained (Tota 2004(Tota , 2005. As Tota puts it:…”
Section: Bringing With and Protectingmentioning
confidence: 99%
“…Researchers who have examined individuals’ autobiographical recollections have found that social context, group identification, and media are important in shaping memory. In a study of the recollections of Studebaker employees, Bodnar (1989) finds memories of managers and workers to be quite different, Other qualitative research shows generation, social location, and the memories reported by others in one’s group are crucial in shaping what individuals remember from the past (Krull and Kobayashi 2009; Spillman and Conway 2007; Tota 2005). Oral historians find that individual life narratives develop as one fits their own past into cultural narratives about their group (Green 2004).…”
Section: Relevant Researchmentioning
confidence: 99%
“…While the left-wing terrorism has been extensively inscribed in the Italian and in the international public discourse, Tota, 2005a [3]). For example, the terrorist attack on Train 904 (23 dicembre 1984) in Val di Sambro has been almost totally forgotten, even if it happened only three decades ago, due to the very active and efficient cultural amnesia instigated by some camorra's clans (Tota, 2005b) [4].…”
Section: Introductionmentioning
confidence: 99%